HUBUNGAN MORFOLOGI OTOT KAKI HUBUNGAN MORFOLOGI OTOT KAKI DAN FLAT FOOT POSTURE DENGAN STABILITAS FUNGSIONAL DAN KEJADIAN ANKLE SPRAIN PADA ATLET - Sugiarta, Githa; Adhitya, I Putu Gde Surya; Paramita, Indah (Kinetic and Physiotherapy Comprehensive, 2024)
Background: An ankle sprain is the most common injury in athletes, and the relationship between foot muscle morphology and flat foot posture with functional stability and the incidence of ankle sprain in athletes is an interesting topic in the world of sports. This study aimed to determine the relationship between foot muscle morphology and flat foot posture with functional stability and the incidence of ankle sprain. Methods: This study used a literature review method. By using secondary data in the form of research journals obtained from various database sources on the internet. The search for literature articles was carried out online on PubMed and Google Scholar sites using the keywords “ankle sprain,” “flat foot posture,” “functional stability,” and “morphology muscles.” Results: After reviewing four articles, it was found that ultrasonography (USG) was a reliable diagnostic method to examine the morphology of muscles (peroneus), which serve as ankle stability. In addition to muscle morphology, athletes with flat foot posture also have a higher risk of ankle sprain due to uneven load distribution and low functional stability.  Conclusion: There is a relationship between foot muscle morphology and muscle activity in athletes with pes planus (flat foot) conditions with functional stability and the risk of ankle sprain in athletes.